2017
DOI: 10.1007/s11356-017-8683-4
|View full text |Cite
|
Sign up to set email alerts
|

Unique characteristics of algal dissolved organic matter and their association with membrane fouling behavior: a review

Abstract: Over the last several decades, the frequent occurrence of algal bloom in drinking water supplies, driven by increasing anthropogenic input and climate change, has posed serious problems for membrane filtration processes, resulting in reduced membrane permeability and increased energy consumption. It is essential to comprehensively understand the characteristics of algal dissolved organic matter (DOM) and the subsequent effects on the filtration processes for better insight into membrane fouling mitigation. Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…Six thiols (mercaptoacetic acid, cysteine, homocysteine, N-acetyl-cysteine, mercaptoethane-sulfonate, and glutathione) were detected with total concentrations of 7-153 nM in boreal lake waters Björn 2014, Liem-Nguyen et al 2015). Recent studies have shown that several green algae excrete some ligands, particularly thiol-containing ligands that form strong complexes with Hg species and thus modify Hg speciation and bioavailability (Mangal et al 2016, Ly et al 2017, Mangal et al 2019a).…”
Section: Mercury Complexation By Biomolecules Produced By the Phytopl...mentioning
confidence: 99%
“…Six thiols (mercaptoacetic acid, cysteine, homocysteine, N-acetyl-cysteine, mercaptoethane-sulfonate, and glutathione) were detected with total concentrations of 7-153 nM in boreal lake waters Björn 2014, Liem-Nguyen et al 2015). Recent studies have shown that several green algae excrete some ligands, particularly thiol-containing ligands that form strong complexes with Hg species and thus modify Hg speciation and bioavailability (Mangal et al 2016, Ly et al 2017, Mangal et al 2019a).…”
Section: Mercury Complexation By Biomolecules Produced By the Phytopl...mentioning
confidence: 99%
“…The main cause of low recoveries from water reclamation is membrane fouling by autochthonous organic matter produced during biological wastewater treatment. 8,9 This type of organic matter has a high membrane fouling potential and is primarily composed of the extracellular polysaccharides that are responsible for floc formation in activated sludge processes. 10,11 High-efficiency reverse osmosis (HERO) may be able to reduce membrane fouling by autochthonous organic matter and prevent biofilm growth on RO membranes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Low recoveries are problematic because they decrease the amount of recoverable water and increase the amount of concentrate solutions requiring treatment or disposal. The main cause of low recoveries from water reclamation is membrane fouling by autochthonous organic matter produced during biological wastewater treatment. , This type of organic matter has a high membrane fouling potential and is primarily composed of the extracellular polysaccharides that are responsible for floc formation in activated sludge processes. , …”
Section: Introductionmentioning
confidence: 99%
“…EEM-PARAFAC has recently become a popular and useful tool to probe the dynamic changes in EfOM for natural and engineering systems [4,[24][25][26]. However, EEM-PARAFAC is not able to reflect non lightabsorbing constituents (e.g., (poly)saccharides) [27]. Size exclusion chromatography (SEC) equipped with organic carbon detector (SEC-OCD) [28] can be a good complementary tool to overcome the limitation.…”
Section: Introductionmentioning
confidence: 99%